Chapter 10 Ageism and Sexuality (2018)
Sexuality remains important throughout a person’s life, but sexual behavior does not receive the same levels of acceptance at all ages. Older people are challenged by ageist attitudes and perceptions that hinder their sexual expression. They are stereotyped as non-sexual beings who should not, cannot, and do not want to have sexual relationships. Expressing sexuality or engaging in sexual activity in later life is considered by many in society as immoral or perverted. False expectations for older people also stem from ideals of beauty, centralization of the biomedical perspective on sexuality of older adults, and the association of sex with reproduction. Unfortunately, older people internalize many ageist attitudes towards sexuality in later life and become less interested in sex and less sexually active. The following chapter explores attitudes towards sexuality in later life among the media, young people, older people themselves, and care providers. In order to enable older people to express their sexuality and sexual identity freely and fully, awareness of ageist perceptions must be raised and defeated.